The present and future disease burden of hepatitis C virus (HCV) infections with today's treatment paradigm – volume 2. (January 2015) - Hatzakis, A.; Chulanov, V.; Gadano, A. C.; Bergin, C.; Ben‐Ari, Z.; Mossong, J.; Schréter, I.; Baatarkhuu, O.; Acharya, S.; Aho, I.; Anand, A. C.; Andersson, M. I.; et al.
Summary: Morbidity and mortality attributable to chronic hepatitis C virus (HCV) infection are increasing in many countries as the infected population ages. Models were developed for 15 countries to quantify and characterize the viremic population, as well as estimate the number of new infections and HCV related deaths from 2013 to 2030. Expert consensus was used to determine current treatment levels and outcomes in each country. In most countries, viremic prevalence has already peaked. In every country studied, prevalence begins to decline before 2030, when current treatment levels were held constant. In contrast, cases of advanced liver disease and liver related deaths will continue to increase through 2030 in most countries. The current treatment paradigm is inadequate if large reductions in HCV related morbidity and mortality are to be achieved.